The Reproduction Performance of Tegal Duck Based on Hematology Status - Ismoyowati, Ismoyowati; Yuwanta, Tri; Sidadolog, J HP; Keman, S (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2006)
The experiment was conducted to study the physiological indicator of Tegal duck based on the hematological parameters and its relation to reproduction performances. The research materials were 20 heads of male and 100 heads of female Tegal ducks. Parameters measured were erytrocyte, leucocyte, differential leucocyte, hemoglobin, hematocrit, protein total, albumin and globulin, and reproduction performances (semen volume and egg production). Method of the research was experimental with Completely Randomized Design, and data were analysed using analysis of variance and correlation. The result of the experiment showed that hematological parameters of Tegal duck that had high production were high significantly (P<0,05) different than the others, except on albumin value. It was concluded that reprodution performances of Tegal duck was highly affected by its hematologys status. (Animal Production 8(2): 88-93 (2006) Key Words: Reproduction performances, Tegal duck, hematology status